Cultivation of Maggots from Organic Waste an Opportunity to Improve Community Economy - Lesna Purnawan; Jaka Slametan; Agus Suyanto; Caesar Rismanto; Susilowati (The International Journal of Education Management and Sociology, 2025)
The cultivation of maggots (Hermetia illucens) from organic waste represents an innovative and sustainable solution to both environmental and economic challenges faced by local communities. This study explores maggot farming as a means of converting organic waste into valuable resources such as animal feed and organic fertilizer, while simultaneously creating new income opportunities for the community. The maggot cultivation process not only reduces the volume of household and market waste but also provides an environmentally friendly alternative for waste management. The results show that maggot farming can significantly contribute to improving community welfare by generating additional income, promoting green entrepreneurship, and supporting a circular economy. Therefore, maggot cultivation from organic waste holds great potential as an effective strategy for sustainable economic empowerment and environmental preservation at the community level.